Jeszcze raz o Borysie Godunowie Aleksandra Puszkina - Stachurka, Małgorzata (Acta Polono-Ruthenica, 2006)
The tragedy Borys Godunov should be admitted to be a picture of an essential culture space. The drama represents generally accepted stereotypes and patterns refering to the Polish nation, however it pays attention to diversity of meaning of Pushkin’s attitude towards Poland. The poet contrasted in the work culture and customs of both nations, he chose heroes, whose names and behaviour evoked readers’ doubts and associations with the biography of Pushkin. Characters of the drama are among others: the fictitious son of Andrzej Kurbski - the Kazakh hero, the nobleman Sobański - in all probability related to the emissary Karolina Sobańska, mysterious and susceptible of various interpretations Piotr Łukicz Chruszczow. Present Pushkin’s texts researches confirmed, that impossible is univocal defining the poet’s mutual relations to Poland and the Polish. Pushkin’s views on the Polish matter differed from his personal connections with Mickiewicz’s compatriots, but, probably, he had the invariable and finally specified opinion on the real weight of the Republic of Poland’s culture and its meaning for Russia and Western Europe.